The Routledge companion to technology management - Daim, Tugrul Unsal, 1967-; Dabić, Marina; Su, Yu-Shan (Routledge companions in business, management and marketing, 2022)
"Bringing together an international range of expertise, this comprehensive Companion to technology management is designed to facilitate the development of management frameworks adaptable for a wide range of organizations, as well as an overview of the development and integration of technology in advanced and emerging economies. Research-based and drawing on a range of practical tools and international cases, it covers the diverse spectrum of the challenges of technology management and how to approach them: I. Fundamentals of Technology Management provides an overview of the fundamental aspects of technology management II. Technology Planning focusses on technology driven organizations, government labs and universities III. Technology Evaluation: including evaluation and assessment, adoption, and forecasting through management tools IV. Technology Development and Transfer: including integration, marketing and intellectual property management V. Managing Technological Innovations: addresses policy, open innovation and technology entrepreneurship. VI. Society and Technology Management: focusses on social issues which impact technology and its management. VII. New Technologies and Emerging Regions: includes blockchain, biotechnologies and smart cities. This Companion is an essential comprehensive source of new and emerging approaches for researchers and advanced students in engineering and technology management, as well as professionals seeking an authoritative global reference source"--